2019
DOI: 10.17116/oftalma2019135052177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal injections of ranibizumab and aflibercept on the retinal nerve fiber layer in patients with concomitant neovascular age-related macular degeneration and glaucoma

Abstract: Цель исследования-изучить влияние ранибизумаба и афлиберцепта на толщину слоя нервных волокон сетчатки (СНВС) у пациентов с неоваскулярной формой возрастной макулярной дегенерации (нВМД) и первичной открытоугольной глаукомой (ПОУГ). Материал и методы. Обследовано 62 пациента (62 глаза) с нВМД в сочетании с ПОУГ. Пациенты были разделены на две группы в зависимости от анти-VEGF-препарата: 1-я группа включала 42 человека (42 глаза), получавших инъекции ранибизумаба; 2-ю группу составили 20 человек (20 глаз), полу… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…1 To date, the potentially damaging effects of repeated intravitreal anti-VEGF injections on glaucoma progression of patients with pre-existing glaucoma or ocular hypertension has been evaluated seldomly. [2][3][4][5][6][7][8] Previous studies on this matter have used metrics such as RNFL thickness to investigate this potential incremental damage to the optic nerve of patients with glaucoma spectrum diseases (GSD). These studies presented conflicting results and several only reported the effect of regular anti-VEGF intravitreal injections in the injected eye group, with no control for comparison.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…1 To date, the potentially damaging effects of repeated intravitreal anti-VEGF injections on glaucoma progression of patients with pre-existing glaucoma or ocular hypertension has been evaluated seldomly. [2][3][4][5][6][7][8] Previous studies on this matter have used metrics such as RNFL thickness to investigate this potential incremental damage to the optic nerve of patients with glaucoma spectrum diseases (GSD). These studies presented conflicting results and several only reported the effect of regular anti-VEGF intravitreal injections in the injected eye group, with no control for comparison.…”
Section: Dear Editormentioning
confidence: 99%
“…These studies presented conflicting results and several only reported the effect of regular anti-VEGF intravitreal injections in the injected eye group, with no control for comparison. 4,6,7 Thus, their methodology to answer this relevant question was questionable, and further higher quality evidence on this topic was required. RNFL thickness, as with most metrics in the human eye, is not static and presents age-related changes throughout time.…”
Section: Dear Editormentioning
confidence: 99%